Imagining a Democratic Future, Forgetting a Worrisome Past: Educational Policy, School Textbooks, and Teachers under the Franco Regime. (February 2014) - Groves, Tamar; Milito Barone, Cecilia
<x content-type="archive" xml:space="preserve">Abstract</x> In 1970 the Franco regime enacted the General Law of Education. The law was one of the dictatorship's attempts to cultivate a liberal image that would lend legitimacy to its authoritarian political project. The declared main aspiration of the reform was to democratize education. However, at the time when this liberal text was published, the dictatorship was struggling for survival and its liberal gestures were accompanied, side-by-side, by the old mechanisms of political oppression. Opposition groups of teachers criticized the inherent shortcomings of the law as well as its application, and offered their own projects for the democratization of Spanish society. In this article we analyze these two educational projects, highlighting how both used the term "democracy" to express distinct, contradictory, and sometimes overlapping meanings. This range of meanings serves to illustrate the complexity of the concept of democratic education in the earliest stages of Spain's transition to democracy.